Tahun Kedua COVID-19: Dampak Pandemi, Kelelahan Zoom, dan Kesehatan Mental Mahasiswa - Kusrohmaniah, Sri; Utami, Muhana Sofiati; Yolanda, Gita; Bima, Destra Riyan Putu Arya; Yakub, Nur Asyikin; Ilmi, Sholikhatul (ANIMA Indonesian Psychological Journal, 2026)
Entering its second year, the COVID-19 pandemic continues to impact various aspects of life. This includes student life, both academically and mentally. This study aims to describe the mental health conditions of students in the second year of the COVID-19 pandemic and compare Zoom fatigue between early and late cohorts of students. The study method used was a cross-sectional survey with descriptive and comparative analysis techniques on 102 students aged 17-22 years. Study participants were given online screening utilizing three standardized instruments, namely: (1) DSM-5 Self-Rated Level 1 Cross-Cutting Symptom Measure; (2) Zoom Exhaustion and Fatigue Scale Indonesian version (ZEF Scale); and (3) Impact of Event Scale COVID-19 version (IES-COVID-19). The study results showed that 92% of study participants experienced Zoom fatigue at a Moderate to High level, while there was no significant difference in the mean Zoom fatigue score when viewed by student cohort (t(100) = .74, p = .46, d = .15). 61% of the study participants reported Moderate to Severe psychological impacts related to COVID-19. The most prevalent symptoms were depression and anxiety. These findings indicate that the mental health of university students in the second year of the COVID-19 pandemic is quite concerning, and that attention and monitoring are required, including the development of mental health intervention programs and higher education policies that are more adaptive to the challenges of online learning and pandemic-related stress.